Projeto Aluno Especial II da UFSM: educação e envelhecimento - Roos, Simone Neiva Milbradt (2017)
This dissertation had as subjects of research the education and the process of aging and its discussions were built from the theoretical contributions of Gerontology. The aim was to investigate the relationship of education through continuing education offered by the Special Student Project II for the aging of the elderly with this academic link. The methodology had as a theoretical-methodological approach the qualitative research, because it was a type of research that understood the social phenomena from the analysis of the subjects, the Special Student II, from his/her perceptions and understanding of reality. The Federal University of Santa Maria came as a pioneer in opening space for the elderly, offering them the possibility to take classes through Resolution 11/92, regardless of the achievement of proof and minimum schooling. From the point of view of four elderly people (Special Students II), the project's founder and the representative of the Department of Registration and Academic Control, this research will offer the institution subsidies so that the continuing education, especially related to aging, can be even more qualified. Among the results, we highlight the subsidies that it is still necessary to expand the dissemination and create new projects for the elderly public in UFSM. Therefore, the the Special Student Project II offers continuing education and relies on students to believe that there is always time to learn and that knowledge makes progress in life enabling new discoveries and personal achievements.